Tętniaki prosówkowate Lebera – opis przypadku (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
We present a case of 21 years old male with significant unilateral decrease of vision. Ophthalmoscopic examination revealed distinct macular edema and peripheral retinal edema. Fluorescein angiography showed peripheral retinal telangiectasia, arteriolal and venous shunts and large areas of hypoperfusion. Base on that picture, diagnosis of miliary Leber aneurysms was made. It followed by laser photocoagulation of retina: macular GRID and peripheral scatter. After 4 months return of normal visual acuity was noted, as well as lack of retinal edema in fluorescein angiography.